Clinical Forensic Examination on Mass Violence’s Victim With Head and Ocular Injury (A Case Report) - Syarifah, Mustika Chasanatusy; Yudianto, Ahmad (UNUSA Press, 2019)
Introduction: Clinical forensic medicine is a branch of medicine that applies medicine to uphold justice in the case of living victims. In accordance with this understanding, the handling of cases of living victims, especially victims of crime, must involve doctors in the field of forensics, in addition to doctors in other fields according to their competence. With so many cases of violent crime, a doctor must be able to provide a report on the results of the examination to the legal apparatus to assist in the judicial process. Case: A man, aged 44 years, found bruises on right eyelid, left eye, left cheek, left and right scalp; blisters on the left and right eye membranes; a cut wound on the right eye membrane and the left eyelid; bleeding under the thick membrane of the brain and swelling of the brain. Discussion: Injuries can occur as a result of violence perpetrated by criminal offenses, such as cases of theft by violence, murder, traffic accidents or ill-treatment. The doctor must be able to mention that the wound examined is caused by sharp violence, blunt force, electrical trauma, thermal trauma, chemical trauma, or other causes of trauma. Determination of the magnitude of the effect of injury to the victim, related to criminal sanctions that will be imposed on the perpetrators of criminal acts. The head is an organ that is often the target of violent blunt crimes. The brain and the surrounding layers are easily susceptible to trauma, resulting in death compared to other body parts. The wound is in accordance with Criminal Code article 90 concerning serious injuries, which results in injuries that do not give any hope of healing at all.